2022
DOI: 10.1186/s12885-022-09720-z
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of functional outcome for patients with newly diagnosed grade 2 or 3 gliomas with co-deletion of 1p/19q – IMPROVE CODEL: the NOA-18 trial

Abstract: Background Given the young age of patients with CNS WHO grade 2 and 3 oligodendrogliomas and the relevant risk of neurocognitive, functional, and quality-of-life impairment with the current aggressive standard of care treatment, chemoradiation with PCV, of the tumour located in the brain optimizing care is the major challenge. Methods NOA-18 aims at improving qualified overall survival (qOS) for adult patients with CNS WHO grade 2 and 3 oligodendro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…The IMPROVE-CODEL/NOA-18 trial aspires to prove the superiority of lomustine and temozolomide (CETEG) plus RT-PCV at progression over RT-PCV as determined at the level of overall survival without sustained functional deterioration for patients with oligodendroglioma [ 34 ]. The combination of lomustine and temozolomide has been proven to be beneficial over temozolomide in patients with MGMT promotor methylated glioblastoma in the NOA-09/CETEG trial [ 35 ] and is currently evaluated in patients with 1p/19q codeletion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IMPROVE-CODEL/NOA-18 trial aspires to prove the superiority of lomustine and temozolomide (CETEG) plus RT-PCV at progression over RT-PCV as determined at the level of overall survival without sustained functional deterioration for patients with oligodendroglioma [ 34 ]. The combination of lomustine and temozolomide has been proven to be beneficial over temozolomide in patients with MGMT promotor methylated glioblastoma in the NOA-09/CETEG trial [ 35 ] and is currently evaluated in patients with 1p/19q codeletion.…”
Section: Resultsmentioning
confidence: 99%
“…WHO grade 4 astrocytomas present a new entity and it is currently unclear whether these tumors should be treated with concomitant temozolomide [ 57 ] or adjuvant temozolomide only [ 27 ]. Besides this, the role of upfront combinatorial chemotherapy without early radiotherapy for chemosensitive oligodendroglioma is currently being answered in the IMPROVE-CODEL trial [ 34 ]. However, these combinatorial treatments are not curative for most patients and progression is likely at some point in time.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges include repeated disappointments in the development of new treatment options, particularly immunotherapies and targeted therapies, none of which have so far improved on the available therapies ( 79 , 126 ). For a substantial number of potential treatment choices, evidence is not (yet) available or remains inconsistent, including, for example, uncertainty around managing oligodendrogliomas without initial radiotherapy or the potential interchangeability of PCV and TMZ in these patients ( 196 ). The most recent WHO classification increases the complexity of choosing treatments based on evidence, as newly defined glioma types and subtypes may not map directly to past trials that used prior classifications ( 86 ).…”
Section: Discussionmentioning
confidence: 99%
“…The exploration of 1p/19q codeletion is not only helpful for the diagnosis of gliomas, but also helps to clarify the mechanism of the disease and guide clinical treatment [29][30][31]. For example, researchers have observed that 1p/19q codeletion patients are likely to respond well to the temozolomide chemotherapy [32], although the exact reason is unclear. Thanks to the rapid progress of high-throughput sequencing technology, our understanding of transcriptional changes in glioma has improved signi cantly.…”
Section: Discussionmentioning
confidence: 99%